TENCON 2006 - 2006 IEEE Region 10 Conference 2006
DOI: 10.1109/tencon.2006.343764
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of Protective Devices in Power Distribution Systems for Reliability Purpose

Abstract: This paper presents the reliability study of failure rate, mean time to failure (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The number of failures is too small for a precise determination of the parameters of the distribution. Tippachon et al studied failures of protective devices such as circuit breakers, disconnectors and fuses and found that the failures follow a Weibull distribution with a shape parameter between 0.5 and 1 [33]. Choonhapran and Balzer developed a Markov model of circuit breakers with five different failure modes, which follow mainly an exponential distribution [34].…”
Section: A Failure Statistics About Circuit Breakersmentioning
confidence: 99%
“…The number of failures is too small for a precise determination of the parameters of the distribution. Tippachon et al studied failures of protective devices such as circuit breakers, disconnectors and fuses and found that the failures follow a Weibull distribution with a shape parameter between 0.5 and 1 [33]. Choonhapran and Balzer developed a Markov model of circuit breakers with five different failure modes, which follow mainly an exponential distribution [34].…”
Section: A Failure Statistics About Circuit Breakersmentioning
confidence: 99%
“…The variable (see Table 3) represents the switched failure probability of the triacs T rk . The parameters of Table 2 are chosen according to the values defined in the papers [18][19][20]. These papers describe more particularly specific reliability analysis of IGBT, thyristor, fuses and capacitors.…”
Section: Reliability Analysismentioning
confidence: 99%
“…If we know scale and shape parameter, then we could plug them into (1) and calculate F (the probability of failure) at any time, t. According to [9], the Weibull parameters a and b can be estimated from PQ data.…”
Section: R(t)=1 -F(t)mentioning
confidence: 99%
“…3 shows the survival probability plot of PEA distribution system over a 12-month period in 2005 for A and B substation both TP1&2 (22kV) for SEMI-F47 curve. The Weibull parameters a and b using [9] and PQ data in Fig. 3 are shown in Table V.…”
Section: R(t)=1 -F(t)mentioning
confidence: 99%